1979
DOI: 10.1111/j.1365-2125.1979.tb04772.x
|View full text |Cite
|
Sign up to set email alerts
|

Mean steady‐state plasma concentrations of labetalol in patients undergoing antihypertensive therapy.

Abstract: 1 Mean steady‐state plasma concentrations of labetalol (labetalol Css) in 17 hypertensive patients undergoing chronic treatment with this drug, have been examined in relation to dose, fall in BP, and beta‐ blockade. 2 A significant relationship (rs = 0.81, P less than 0.001) was observed between labetalol Css and daily dose. 3 No correlation was found between labetalol Css and antihypertensive response. 4 In thirteen patients, there seemed to be significant relationship between labetalol Css and beta‐blockade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
(2 reference statements)
1
1
0
Order By: Relevance
“…There is some evidence of a relationship between steady-state plasma labetalol levels and blood pressure control in that most, but not all, patients with lower steady-state levels on a given dose required higher maintenance doses to achieve blood pressure However, in the study of Sanders and colleagues, no correlation was found between the steady-state concentration of labetalol and the antihypertensive response. 61 In this study the degree of beta-adrenoceptor blockade, measured as isoproterenol CD, , , paralleled the changes in plasma labetalol concentration.…”
Section: Pharmacodynamic Propertiessupporting
confidence: 53%
“…There is some evidence of a relationship between steady-state plasma labetalol levels and blood pressure control in that most, but not all, patients with lower steady-state levels on a given dose required higher maintenance doses to achieve blood pressure However, in the study of Sanders and colleagues, no correlation was found between the steady-state concentration of labetalol and the antihypertensive response. 61 In this study the degree of beta-adrenoceptor blockade, measured as isoproterenol CD, , , paralleled the changes in plasma labetalol concentration.…”
Section: Pharmacodynamic Propertiessupporting
confidence: 53%
“…4) and this probably explains why some investigators have claimed that no such relationship exists (Lund-Johansen and Bakke, 1979;Sanders et al, 1979). However, McNeil (1981), examining the dose response-relationship in patients receiving twice daily doses ranging from 200 to 1200mg, found a clear relationship between the plasma drug concentration and the fall in blood pressure, especially in the upright position ( fig.…”
mentioning
confidence: 92%